(untitled) (Revista Brasileira de Contabilidade e Gestão, 2016)
The presence of individual investors in the main Brazilian stock exchange has increased in recent years. The vast majority are small investors who do not always have knowledge or resources to analyze in depth the assets in which they invest. The aim of this study is to verify the efficiency of the application in the Brazilian market of two strategies used by successful investors. As well, the use of a simple tool to evaluate and active assist in the composition of a portfolio to minimize the risks. To do so, the theories Benjamin Graham to choose the assets to be acquired, and the model of Harry Markowitz efficient frontier were used to define the contribution of each asset in the portfolio composition. For the calculations to Excel ® spreadsheet was used, a simple and affordable tool for all investors. The study period were the years 2006 to 2010, ie two years prior and two years following the global crisis of 2008. At the beginning of the period were formed five portfolios as filters Graham and the share of each asset was established as the criteria stated by Markowitz. The assets comprising the portfolio as well as its share in total investment are evaluated and changed only once at the beginning of each year.